Pembatalan Pesanan Pada Jual Beli Online Sistem Cash On Delivery (COD) Perspektif Hukum Ekonomi Syariah (Studi Kasus Pada Toko Online Sweeter Shop di Kecamatan Kalisat) - Mohammad Firmansyah; Nurul Izah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
One of the advantages or advantages of online buying and selling activities with the current cash on delivery (cod) system is very helpful for everyone in terms of meeting all their needs. By only capitalizing on waiting for the order to arrive at home and being paid after the goods arrive at the hands of consumers. However, in addition to these positive things, there are also several risks arising from transactions using the cash on delivery (cod) system, one of which is canceling the order even though the goods have reached the consumer's address. This also happened in the online shop "sweeter shop" in Glagahwero Village, Kalisat District. The problems in this study are How is the practice of canceling orders in online buying and selling Cash On Delivery (COD) system at the Online Shop "Sweeter Shop" in Kalisat District and how is the view of muamalah fiqh on the cancellation of orders in online buying and selling Cash On Delivery (COD) system. The research method used is using a qualitative approach. In determining data sources using purposive techniques, while the data collection methods used are interview, observation and documentation methods. The conclusions of this study are: that the practice of canceling orders with a COD payment system includes a Wakalah Bil 'Ujrah contract and occurs due to a fasakh. The cancellation is also motivated by several reasons, namely that the goods displayed on social media do not match what consumers receive, the budget is not enough and the buyer has other options. According to the concept of fasakh, cancellation in a sale and purchase transaction is permitted as long as there is an attitude of an taradhin (mutual willingness) between the two parties.